2014
DOI: 10.17275/per.14.10.1.2
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship between Internet Addiction and Depression Levels of High School Students

Abstract: The concept of internet addiction refers to the excessive use of internet which in turn causes various problems in individual, social and professional aspects. The aim of this study is to determine the relationship between depression and internet addiction in terms of grades, sex, the existence of internet connection at home and time spent on internet. The study used survey model. The study group consisted of 369 adolescents from three high schools of different socioeconomic background. Data was collected by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…It has been further determined that compulsive/heavy Internet users obtain higher scores in depression than average Internet users. The results of the present study are in line with most findings in this area (8)(9)(10). The depression scale in the MMPI mostly indicates symptoms, such as isolation, low efficiency, difficulty in expressing desires, tendency to social isolation, excessive anxiety, and humility.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been further determined that compulsive/heavy Internet users obtain higher scores in depression than average Internet users. The results of the present study are in line with most findings in this area (8)(9)(10). The depression scale in the MMPI mostly indicates symptoms, such as isolation, low efficiency, difficulty in expressing desires, tendency to social isolation, excessive anxiety, and humility.…”
Section: Discussionsupporting
confidence: 93%
“…The study discovered how Internet dependency is linked to psychological symptoms, such as depression, anxiety, phobias, and physical disorders (8). A positive relationship between Internet dependency and depression was found in the study conducted by Cengiz Sahin on Turkish national students (9). Moreover, another study also found a positive correlation between stress and anxiety and Internet dependency in highschool students (10).…”
Section: Introductionmentioning
confidence: 81%
“…Çelik, Atak, Başal (2012) [66] Интернет-аддикция, патологическое использование сети Интернет, «проблемное» использование сети Интернета, злоупотребление использования сетью Интернет-терминологическое разнообразие, описывающее одну из частных форм поведенческих аддикций. Sahin (2014) [67] Чрезмерное использование ресурсов сети Интернет с утратой контроля, что приводит к развитию различных проблем в личностном, социальном и профессиональном аспектах. Weinstein, Feder, Roseberg, Dannon (2014) [5] Лица, использующие сеть Интернет в течение длительного периода времени добровольно изолируют себя от других форм социальной активности, что приводит к избирательной фиксации на онлайн активности и уходу от повседневных жизненных проблем.…”
Section: таблицаunclassified
“…Bu sonuç doğrultusunda erkek öğretmen adaylarının kadın öğretmen adaylarına göre internetin olumsuz sonuçlarına daha fazla maruz kaldıkları belirlenmiştir. Literatürde erkeklerin kadınlara göre interneti problemli kullanma daha fazla eğilimli olduklarını belirten çok sayıda araştırma (Balta ve Horzum, 2008;Canbaz, Sunter, Peksen ve Canbaz, 2009;Günüç, 2009;Kıran-Esen ve Gündoğdu, 2010;Morahan-Martin ve Schumacher, 2000;Odacı ve Kalkan, 2010;Şahin, 2011, 2014Tahiroğlu, Çelik, Uzel, Özcan ve Avcı, 2008;Tutgun, 2009;Üneri ve Tanıdır, 2011) mevcuttur.…”
Section: Tartışma Sonuç Ve öNerilerunclassified